Preoperative computed tomography assessment for a deep inferior epigastric perforator (DIEP) flap: a new easy technique from the Bologna experience. (October 2021) - Renzulli, Matteo; Clemente, Alfredo; Brocchi, Stefano; Gelati, Chiara; Zanotti, Simone; Pizzi, Carmine; Tassone, Daniela; Cappabianca, Salvatore; Cipriani, Riccardo; Golfieri, Rita
Background: Deep inferior epigastric perforator (DIEP) flap reconstruction is the gold standard reconstructive technique for women undergoing breast cancer surgery. A preoperative computed tomography angiography (CTA)-dedicated protocol and 3D reconstructions are mandatory for correct surgical planning. Purpose: To evaluate the diagnostic performance of a new preoperative CTA protocol and a new reconstruction method in the assessment of DIEP technique. Material and Methods: A total of 263 women (median age 49 years, age range 26–73 years) underwent preoperative CTA examination before DIEP flap breast reconstruction. A CTA-dedicated protocol followed by 3D-reconstructions were performed. Identification, branching pattern, and caliber at origin were assessed for each perforator. Intraoperative findings were the standard of reference. The sensitivity, positive predictive value, and diagnostic accuracy of the preoperative CTA protocol were calculated. Results: In 255/263 (97%) patients, the dominant perforators assessed by CTA resulted adequate for surgical reconstruction. In 260/263 (99%) cases, the imaging localization of the dominant perforators corresponded with those seen intraoperatively (mean errors ≤1 cm). The preoperative CTA imaging sensitivity, positive predictive value, and diagnostic accuracy in determining the localization of perforators were 99% (95% CI 98–100), 100% and 99% (95% CI 98–100), respectively. No statistically significant differences were found between the CTA findings and the surgical findings for the assessment of branching pattern and caliber of the dominant perforators ( P < 0.001). Conclusion: The present protocol has demonstrated high accuracy in the CTA imaging assessment of the perforators before DIEP flap reconstruction with high reproducibility between CT and surgical findings.